2016
DOI: 10.4028/www.scientific.net/msf.854.93
|View full text |Cite
|
Sign up to set email alerts
|

Skin Pass Rolling of High Manganese Steels

Abstract: Applying a specific roughness on steel sheets, to ensure paintability and sufficient lubrication, is a crucial point for the metal forming processes. Due to the strength of high manganese HSD® steels (X70MnAlSi 15-2.5-2.5), special actions are necessary to obtain the required roughness. At Salzgitter Mannesmann Forschung GmbH skin-pass rolling experiments on high manganese HSD® steels with different PRETEX® textured work-rolls were performed to investigate the influence of roll-surface-texture and skin-pass ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
1
0
4
Order By: Relevance
“…Soğuk haddeleme sürecinin son basamağı ve hassas bir sonlandırma süreci olan temper haddeleme işlemi ile endüstride yassı ürün pürüzlendirme işleminde rol üstlenen özel pürüzlendirilmiş merdaneler ve bu merdaneler arasından haddelenerek kalınlığı azaltılan şerit veya sac malzeme söz konusudur. Merdaneler SBT (kumlama yoluyla pürüzlendirme), EDT (elektriksel deşarjla pürüzlendirme), EBT (elektron ışınıyla pürüzlendirme), LT (lazerle pürüzlendime) ve ECD (elektrokrom ile pürüzlendirme) /Topokrom/Pretex [14,16,[28][29][30][31][32] yöntemlerinden herhangi biri kullanılarak özel olarak pürüzlendirilir. Pürüzlü merdaneler arasından yassı ürüne haddeleme parametrelerine bağlı olarak pürüzlülük transferi gerçekleştirilir.…”
Section: Pürüzlendi̇rmeni̇n Endüstri̇deki̇ öNemi̇unclassified
See 3 more Smart Citations
“…Soğuk haddeleme sürecinin son basamağı ve hassas bir sonlandırma süreci olan temper haddeleme işlemi ile endüstride yassı ürün pürüzlendirme işleminde rol üstlenen özel pürüzlendirilmiş merdaneler ve bu merdaneler arasından haddelenerek kalınlığı azaltılan şerit veya sac malzeme söz konusudur. Merdaneler SBT (kumlama yoluyla pürüzlendirme), EDT (elektriksel deşarjla pürüzlendirme), EBT (elektron ışınıyla pürüzlendirme), LT (lazerle pürüzlendime) ve ECD (elektrokrom ile pürüzlendirme) /Topokrom/Pretex [14,16,[28][29][30][31][32] yöntemlerinden herhangi biri kullanılarak özel olarak pürüzlendirilir. Pürüzlü merdaneler arasından yassı ürüne haddeleme parametrelerine bağlı olarak pürüzlülük transferi gerçekleştirilir.…”
Section: Pürüzlendi̇rmeni̇n Endüstri̇deki̇ öNemi̇unclassified
“…Örneğin; 4800 kN/m haddeleme kuvvetinde HSD600 çeliğinin pürüzlülük transferi % 60, HSD900 çeliği için % 30, HSD1100 çeliği için % 27 oranındadır. HC340LA çeliğine ise 2400 kN/m haddeleme kuvvetinde % 91,7 pürüzlülük transfer edildiği gözlenmiştir [16].…”
Section: şEkil 4 Temper Haddelemede Haddeleme Uzaması-malzemeunclassified
See 2 more Smart Citations
“…Some of them are rolling speed, elongation, reduction ratio, properties of the material, roll parameters (roughness, radius, material, roughening method), lubrication conditions, etc. (Wu et al , 2019; Xia et al , 2017; Rodriguez-Vidal et al , 2020; Kijima, 2014; Mekicha et al , 2020; Nagase et al , 2009a; Köhler et al , 2016). Dick and Lenard (2005) concluded that as the rolling speed increased, loads and a forward slip would increase, thereby increasing the surface roughness of the sheets and approaching the value of the roll roughness.…”
Section: Introductionmentioning
confidence: 99%